Benin : Fifth Review under the Extended Credit Facility Arrangement, Request for Extension, and Request for Modification of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Benin's Fifth Review Under the Extended Credit Facility Arrangement, Request for Extension, and Request for Modification of Performance Criteria. Program implementation continues to be very satisfactory. The macroeconomic and structural policies outlined by the authorities are adequate to pursue the program's objectives, and risks to program implementation are deemed manageable. Benin's economic performance remains strong despite a less supportive external environment and the border closure with Nigeria. The significant increase in the share of external debt in total debt in the past two years warrants caution. The recent debt reprofiling operation and the Eurobond issuance have contributed to lowering borrowing costs, diversifying the financing structure, and extending debt maturity. However, these operations can also generate new vulnerabilities that will need to be mitigated through an enhanced debt management strategy and continued capacity improvements at the debt management office.